Immigration of International Students to the EU: Ireland - O'CONNELL, PHILIP J.; FINN, MAIREAD (Report prepared for the European Commission Directorate-General Home Affairs & published by the ESRI)
This study provides an overview of the immigration policies that are being implemented regarding international students. This report is particularly timely in Ireland, as it follows a period of significant policy activity around the provision of education to international students, with developments in relation to immigration, to monitoring and inspections of education providers, to a restructuring of bodies and their functions, and to the work entitlements of international students. These policy changes have aimed to facilitate a greater balance between actively attracting international students to Ireland for the purposes of study and preventing the misuse of international student routes to access the labour market. Key to the Irish International Education Strategy has been the combination of a drive to enhance the quality of international education as well as to strengthen the visa and immigration system. Efforts to prevent misuse of the student route, through time limits on stay and proof of progression, have been matched by an ambitious and far-reaching marketing and promotional strategy, the impact of which is evident in the increased number of bilateral agreements incorporating an education focus in recent years. It is anticipated that this will translate into greater student numbers in the coming years.
PUBLISHED
Keywords: Immigration